2011
DOI: 10.1111/j.1759-6831.2011.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural hybridization and introgression in sympatricLigulariaspecies (Asteraceae, Senecioneae)

Abstract: The difficulty in clarifying species of genus Ligularia Cass. has been attributed to rapid and continuous allopatric speciation in small and isolated populations, combined with interspecific diploid hybridization in the Qinghai‐Tibetan Plateau and adjacent areas. However, no concrete example has been reported to prove this hypothesis. We studied a natural mixed population of six species of Ligularia in which some individuals were morphologically intermediate between L. subspicata and L. nelumbifolia. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…Several cases have been reported where hybrids inherit compounds from both parents [b]. We also reported that hybrids of L. nelumbifolia and L. subspicata produced compounds of both parents additively . In the present case of hybrids of L. cymbulifera and L. tongolensis , the chemical outcome was variable.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Several cases have been reported where hybrids inherit compounds from both parents [b]. We also reported that hybrids of L. nelumbifolia and L. subspicata produced compounds of both parents additively . In the present case of hybrids of L. cymbulifera and L. tongolensis , the chemical outcome was variable.…”
Section: Discussionmentioning
confidence: 47%
“…Hand .‐ Mazz . . Furanoeremophilanes were detected in L. subspicata but not in L. nelumbifolia ; they were detected in the hybrids.…”
Section: Introductionmentioning
confidence: 75%
“…It is endemic to the HMR, with a distribution in northwestern Yunnan and southwestern Sichuan provinces. It usually grows in grasslands, alpine meadows, and forest understories of various environments at altitudes of approximately 2100–4600 m. Ligularia vellerea occurs with a few other congeneric species in some regions, however, no obvious hybridization or introgression has been detected between this species and other co‐occurring species (Yu et al, 2011). Thus, this species is suitable for studying intraspecific diversification in the HMR.…”
mentioning
confidence: 99%
“…Similarly, shared pollinators are observed in sympatric Primula ( P. secundiflora × P. poissonii ), Roscoe ( R. humeana × R. cautleoides ) (Du et al, ; Zhu et al, ). Generalist pollination syndromes are thought in particular to be a key feature for hybridization in Ligularia (Cao, Ma, & Wang, ; Yu, Kuroda, & Gong, ; Yu, Kuroda, et al, ). Therefore, these prerequisites may reduce reproductive barriers and increase the probability for occurrence of hybridization in regions of sympatry for these taxa.…”
Section: Hybrid Zones In the Hmrmentioning
confidence: 99%
“…Moreover, difference in competition of the pollen at the stigmatic surface may facilitate asymmetrical hybridization. The bidirectional and asymmetrical hybridization are suggested in the case of L. subspicata and L. nelumbifolia (Yu et al, ). One of the parents is five times more prevalent than the other in a sympatric zone of Ligularia .…”
Section: Hybrid Zones In the Hmrmentioning
confidence: 99%